Optimal design and development of a fast steering robot inspired by scallops - Wang, Yumo; Gao, Tianyu; Pang, Shunxiang; Xu, Jiajun; Tao, Xiayu; Yang, Junqin; Sheng, Wentao (Frontiers in Bioengineering and Biotechnology, 2024)
The improvement of the steering performance of jet robots is challenging due to single inflexible jet aperture. Scallops provide a potential solution with hard shells and a double-hole jet propulsion, which are expected to achieve fast steering movement under water. Inspired by scallops, a bionic propulsion dynamic mesh is proposed in this article, and a three-dimensional computational model of scallops is established. We further calculated the scallop propulsion mechanism under the swing of shells with different shapes. The coupling of simultaneous swing of two shells and their coupling with velum are presented, revealing the unique movement mechanism of Bivalvia. Based on this, the advantages of the double-hole jet propulsion are applied to develop a scallop robot with excellent steering capabilities. Experiments are conducted to verify the steering performance of the scallop robot.